Representation of Hyperreality in The Collagena Advertisement “No Keriput No Keropos” - Annisarizki; Mardiana, Siska; Putri, Liza Diniarizky (Lingkar Studi Komunikasi (LISKI), 2025)
This study analyzes the representation of beauty constructed in the Collagena advertisement with the tagline “No Wrinkles No Pores” starring Song Hye Kyo using the framework of Jean Baudrillard’s semiotic method to examine the concept of hyperreality that shapes contemporary beauty standards. The Collagena advertisement was analyzed using semiotics with a qualitative approach in 11 scenes in the advertisement that lasted 31 seconds. From the results of the research that the researcher analyzed, it shows that the Collagena advertisement constructs an ideal beauty narrative centered on wrinkle-free skin and strong bones at the age of 25 and above for women, and implies that a woman’s value depends on physical perfection even though she is no longer young. The representation of Song Hye Kyo who appears youthful and seems unaffected by the natural process of aging represents a hyperreal beauty that is difficult to achieve for the majority of Indonesian women. The construction of pseudo-reality depicted in the Collagena advertisement covers up the facts about the biology of the aging process and promotes a consumer ideology, where beauty is commodified and standardized following Korean popular culture. This reveals that this advertisement reinforces unrealistic expectations. It gives rise to consumer behavior, and normalizes media actions to beautify themselves according to Korean beauty standards among Indonesian women who try to adapt to these beauty standards.